Leptospiras isolated from mice Mus musculus brevirostris in the state of Rio de Janeiro, Brazil - Cordeiro, Fernando (Pesquisa Agropecuaria Brasileira, 2014)
A bacteriological study for Leptospira was made on 116 mice (Mus musculus brevirostris Waterhouse 1837) caught in the Seropédica District, Itaguaí Municipality. Forty six or 39.6% were found to be infected by Leptospira. The organisms were isolated 42 times from the kidneys, 6 from the urine and 3 from the blood. After the inoculation of macerated diluted kidneys in Guinea pigs an additional 4 strains were isolated from the blood, 3 from the urine, 4 from the kidneys and 3 from the liver. Direct darkfield examinations showed the presence of leptospiras only 6 times. Fletcher's medium permitted a greater number of isolations, however, Korthof's medium favored a more rapid growth of the organisms. Four strains were studied using the microscopical agglutination test with 15 hyperimune serums. The serotype pomona reacted positively to the test. This serotype had not been found in the wild animals of Brazil. The author believes that the mouse is one of the most wild frequent life reservoirs of leptospiras in the area.